Romolo in pittura (a proposito di Luxor. 325 R2) - SPORTOLARI, Elena (AL. Rivista di studi di Anthologia Latina, 2021)
Abstract The paper examines Luxorius’ epigram 325 R2De Romulo picto, ubi in muris fratrem occidit. The analysis of textual references to the literary tradition about Romulus’ fratricide, allows to discover, despite the laudatory tone of the poem, a controversial interpretation of the founding myths of Rome, that finds correspondence in several African authors, including other poets of the Anthologia Latina.